BANTUAN TEKNIS PELAKSANAAN PENGECATAN BALAI RW XI JALAN SILIKAT KELURAHAN PURWANTORO KECAMATAN BLIMBING KOTAMADYA MALANG - Udi Subagyo; Nain Dhaniarti Raharjo; R, Achendri M.Kurniawan; Moch. Khamim; Boby Asukmajaya Raharjo (Publisher UPT P2M Politeknik Negeri Malang, 2021)
Balai RW is a construction or building used by residents for RT activities or activities of local residents and has been built since 1998 and is used as a place for local residents' activities. For the condition of the Balai RW XI in 2020 today, there are many that are not suitable for use, especially in wall construction, where many conditions are damp and the wall paint is peeling off so that repairs are needed in the form of painting the outer and inner walls. Implementation of Community Service Painting of Balai RW XI Jl. Silikat Kel.. Purwantoro Kec. Blimbing Malang city is carried out are: 1. Calculation of the Budget Plan for Painting Implementation Costs Balai RW XI is Rp. 13,955,000, - (Thirteen Million Nine Hundred Fifty Five Thousand Rupiah) the source of funds from PKM Polinema activities and RW XI Cash. 2. Painting the Balai RW XI is prioritized on repairing inner and outer wall paints. 3. Implementation of painting at Balai RW XI will be carried out from 20 July 2020 - 8 August 2020 with a total processing time of 3 weeks.